The correlation between the quality of anc services and the incident of lbw In the public health center of Wates in Kulon Progo Regency - Fitri Handayani; Herlin Fitriani K (Universitas 'Aisyiyah Yogyakarta, 2019)
In the world of LBW occupies the first cause of infant mortality in the world in the early period of life. LBW accounts for 60% to 80% of all neonatal deaths. The global prevalence of LBW is 20 million per year or 15.5% of all babies born in the world (WHO, 2015). In Indonesia, according to The Inter-Census Population Surveys (SUPAS) 2015 IMR was 22.23 per 1,000 live births (Kemenkes RI, 2016). The Poor quality of antenatal care is one of the risk factors for LBW (Sistiarani, 2008). This study aims to determine the correlation between the quality of ANC services and the incidence of LBW in the Public Health Center of Wates Kulon Progo Regency. This study uses quantitative research with case control design and uses a retrospective approach. The populations of the study were mothers who had given birth to babies during the last two years (2016-2017). The sampling technique uses total sampling for control cases by using a ratio of 1: 1 for the case group of 40:40 samples. The study proves that the results of statistical tests show that there is a relationship between the quality of ANC services and the incidence of LBW with a p-value of 0.025 (OR=3.095, CI= 1.234-7.706).). There is a relationship between the quality of ANC services and the incidence of LBW. The inadequate or unqualified quality of ANC services increases the risk 3 times for the incident of LBW. It is expected to be able to monitor and import data on pregnant women using a mobile application.